Monitoring Pemakaian Daya Listrik Rumah Berbasis IoT - Zakwansyah Zakwansyah; Fitriady Fitriady; Muhammad Agil Haikal (Universitas Darul Ulum, 2024)
The current prepaid and postpaid electrical payment systems still have limitation, in monitoring electrical powerconsumption. In postpaid electricity, recording through officers is still done manuallywhen monitoring electrical power usage, whereas for the prepaid system users cannot know electrical power usage in real time. Based on these conditions, a toolwas designed that capable of calculatingthe electrical power used by using home appliancesin real time and can be monitored remotely. This system is designed using the N. meanwhile, it can beode MCU ESP8266as the main controller and the PZEM-004T sensor to measure voltage (V), current(A), plectrical Powerower (W), and energy (kWh), as well as fees that must be paid (Rp) accordingly. Usage, whre the data will bedisplayed on a 20x4 LCD for on-site monitoring. Meanwhile, it canbe monitored remotely using Blynk IoT application whichis connected to the internet network. Generally this system can work with in error rate of <5%, where testing is carried out for 20 minutes for indescent lamp loads.